Assessment of structure-activity relationships and biased agonism at the Mu opioid receptor of novel synthetic opioids using a novel, stable bio-assay platform - Vasudevan, Lakshmi; Vandeputte, Marthe; Deventer, Marie; Wouters, Elise; Cannaert, Annelies; Stove, Christophe P. (Biochemical pharmacology, 2020)
[Display omitted] Fentanyl and morphine are agonists of the Mu opioid receptor (MOR), which is a member of the GPCR family. Their analgesic effects are associated with unwanted side effects. On a signaling level downstream from MOR, it has been hypothesized that analgesia may be mediated through the G protein pathway, whereas the undesirable effects of opioids have been linked to the β-arrestin (βarr) pathway. Despite being an increasingly debated subject, little is known about a potential ‘bias’ (i.e. the preferential activation of one pathway over the other) of the novel synthetic opioids (NSO) – including fentanyl analogs – that have emerged on the illegal drug market. We have therefore developed and applied a novel, robust bio-assay platform to study the activity of 21 NSO, to evaluate to what extent these MOR agonists show biased agonism and to investigate the potential correlation with their structure. In addition, we evaluated the functional selectivity of TRV130, a purported G protein-biased agonist. We applied newly established stable bio-assays in HEK293T cells, based on the principle of functional complementation of a split nanoluciferase, to assess MOR activation via recruitment of a mini-Gi protein (GTPase domain of Gαi subunit) or βarr2. All but two of the tested NSO demonstrated a concentration-dependent response at MOR in both bio-assays. The developed bio-assays allow to gain insight into the βarr2 or G protein recruitment potential of NSO, which may eventually help to better understand why certain opioids are associated with higher toxicity. Adding to the recent discussion about the relevance of the biased agonism concept for opioids, we did not observe a significant bias for any of the evaluated compounds, including TRV130.